COPD is independently associated with 6‐month survival in patients who have life support withheld in intensive care. (11th May 2018) - Maamar, Adel; Chevalier, Stéphanie; Fillâtre, Pierre; Botoc, Vlad; Le Tulzo, Yves; Gacouin, Arnaud; Tadié, Jean‐Marc
Abstract: Background: In‐hospital outcomes following decisions of withholding or withdrawing in Intensive Care Unit (ICU) patients have been previously assessed, little is known about outcomes after ICU and hospital discharge. Our objective was to report the 6‐month outcomes of discharged patients who had treatment limitations in a general ICU and to identify prognostic factors of survival. Methods: We retrospectively collected the data of patients discharged from the ICU for whom life support was withheld from 2009 to 2011. We assessed the survival status of all patients at 6 months post‐discharge and their duration of survival. Survivors and non‐survivors were compared using univariate and multivariate analyses by Cox's proportional hazard model. Results: One hundred fourteen patients were included. The survival rate at 6 months was 58.8%. Survival was associated with acute respiratory failure (48% vs 19%, P = .006), a history of COPD (40% vs 21%, P = .03) and a lower SAPS II score (44 vs 49, P = .006). We identified a history of COPD as a prognostic factor for survival in the multivariate analysis (HR = 2.1; IC 95% 1.02‐4.36, P = .04). Conclusion: A total of 58.8% of patients for whom life‐sustaining therapies were withheld in the ICU survived for at least 6 months after discharge. Patients with COPD appeared to have a significantly higher survival rate. The decision to withhold life support in patients should not lead to a cessation of post‐ICU care and to non‐readmission of COPD patients.